Small-scale fisheries in the middle River Tocantins, Imperatriz (MA), Brazil - Cetra, M.; Petrere, M. (Blackwell Science, 2001)
The description of the small-scale fisheries in the middle River Tocantins and their dynamics, in a full year cycle, was made out using questionnaires when interviewing fishermen at Imperatriz market. The landed fish exhibited a seasonal pattern related to the hydrological cycle, fishing effort and species diversity. Curimata, Prochilodus nigricans Agassiz, is the most important commercial fish. The fishing gears used in the area are castnets, gillnets, longlines and beach seines. Thirty-six percent of fish landed were caught exclusively by beach seine which mainly targets curimata. Alterations in the physical and biological characteristics of the middle River Tocantins due to the building of the Tucurui dam (2850 km(2) total area) allowed the mapara, Hipophthalmus marginatus Valenciennes, to colonise this area. During the closed season for nets, Siluriformes are the target of the fisheries, caught exclusively by longlining.
Keywords: Brazil; inland fisheries ecology; River Tocantins; small-scale fisheries